Physico-mathematical Conceptual Difficulties A Barrier to Learning ‘Motion’ in Physics among Higher Secondary Students in Kerala - Abdulla, Shyma Usman; N S, Mumthas (JOURNAL OF INDIAN EDUCATION, 2023)
Physics is a difficult school discipline due to the difficulty faced by the students in integrating the concepts of mathematics and physics (Mwangala and Shumba, 2016). This study provides insights into higher secondary students’ difficulties when solving physics problems involving the application of mathematical concepts. The data required for the investigation was gathered using ‘Physicomathematical Conceptual Test’ with 70 multiple choice questions based on select basic concepts from ‘Motion’. The test was conducted on 880 higher secondary students who were sampled using stratified sampling technique from various districts of Kerala. The study showed that the extent of physicomathematical conceptual difficulties in total and in the sub-categories, viz., ‘creating or identifying the formula’, ‘extracting information from diagrams or graphs’, ‘creating schematic diagrams or graphs’ and ‘application of mathematics’, are moderate. The extent of each category of difficulty in the respective topics was also studied to rank them.